Innovative art teaching with augmented reality: validation and effectiveness of an ar-based embossing art module for vocational high schools - Yekti , Dony Pamungkas; Rahayuningtyas, Wida; Sayekti , Pranti (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
This study addresses the limited creativity in art learning at Muhammadiyah 1 Vocational High School Kepanjen by developing and evaluating an Augmented Reality (AR)--based teaching module for embossing techniques. The research, conducted using the ADDIE model within a Research and Development (R&D) framework, involved 26 Grade X students majoring in Network Computer Engineering. It focused on enhancing specific aspects of creativity, including originality, technical skills, and conceptual understanding. Validation by media and material experts yielded high scores of 89.3% and 91.3%, respectively. The module's effectiveness was demonstrated through significant improvements in student outcomes, with an average post-test score of 85.43 compared to a pre-test score of 66.95. The AR module fosters an engaging and immersive learning experience by combining interactive multimedia elements, bridging traditional art techniques with modern technology. This research contributes to the advancement of vocational art education by promoting creativity and cultural heritage preservation through innovative digital tools.